Ultimate light-shining-through-a-wall experiments to establish QCD axions as the dominant form of dark matter - Hoof, Sebastian; Jaeckel, Joerg; Lucente, Giuseppe (Physical review, 2025)
Establishing the axion as the dark matter (DM) particle after a haloscope discovery typically requires follow-up experiments to break the degeneracy between the axion’s coupling to photons and its local DM abundance. Given that a discovery would justify more significant investments, we explore the prospects of ambitious light-shining-through-a-wall (LSW) setups to probe the QCD axion band. Leveraging the excellent mass determination in haloscopes, we show how to design LSW experiments with lengths on the order of 100 km and suitably aligned magnetic fields with apertures of around 1 m to reach well-motivated axion models across up to four orders of magnitude in mass. Beyond presenting a concrete plan for postdiscovery experimental efforts, we briefly discuss complementary experiments and future directions beyond LSW experiments.
Gesehen am 27.08.2025